2017
DOI: 10.1371/journal.pone.0185537
|View full text |Cite
|
Sign up to set email alerts
|

The use of antenatal care in two rural districts of Upper West Region, Ghana

Abstract: BackgroundDespite decades of implementation of maternity healthcare programmes, including a focus on increasing the use of antenatal care (ANC) and concomitant birth preparedness and complication readiness (BPCR), the uptake of ANC continues to be below expectations in many developing countries. This has attendant implications for maternal and infant morbidity and mortality rates. Known barriers to ANC use include cost, distance to health care services and forces of various socio-cultural beliefs and practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
9
30
0
Order By: Relevance
“…The difference across studies might be related with the utilization of antenatal care services across countries. For instance, a study conducted in Ghana indicated that a higher proportion of pregnant women were completed four or more antenatal care visits compared to a study conducted in Ethiopia (41.3% vs 33.0%) (46,47). Moreover, the risk of giving birth for a small newborn baby for gestational age among women with PIH was higher; this could be related with intrauterine growth retardation due to a decrease of uteroplacental blood flow and the development of ischemia in women with pregnancy-induced hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…The difference across studies might be related with the utilization of antenatal care services across countries. For instance, a study conducted in Ghana indicated that a higher proportion of pregnant women were completed four or more antenatal care visits compared to a study conducted in Ethiopia (41.3% vs 33.0%) (46,47). Moreover, the risk of giving birth for a small newborn baby for gestational age among women with PIH was higher; this could be related with intrauterine growth retardation due to a decrease of uteroplacental blood flow and the development of ischemia in women with pregnancy-induced hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…An estimated 99% of all maternal deaths occur in developing countries and more than half occur in sub-Saharan Africa (SSA) [1]. Developing countries continue to grapple with a huge burden of maternal and child mortalities where approximately 800 girls and women died as a result of pregnancy and childbirth-related complications in 2015 in SSA [2].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization predicts a world where every pregnant woman and newborn receives quality care throughout the pregnancy, childbirth, and the postnatal period (WHO, 2016a). There is widespread evidence that antenatal care (ANC) is very crucial in the reduction of maternal mortality and morbidity (Miltenburg et al, 2017;Sumankuuro et al, 2017). The recommendations of World Health Organization (WHO) on maternal health care promotion interventions encourage active male partner involvement in ANC delivery as well as postnatal care to improve upon the health outcome of both mothers and their children (WHO, 2016a).…”
Section: Introductionmentioning
confidence: 99%